The Theoretical and Applied Approach of International mobility of Students in Algerian Universities under the Current Reform of Higher Education –the Model of LMD System– - بخوش , وليد (Milev Journal of Research and Studies, 2019)
The objectives of this study are to examine the mobility of students at the Algerian University, particularly the international mobility, which is one of the most important objectives of the LMD system, which is one of the most recent reforms adopted by the Algerian University in its new engineering of higher education. The research question is: What is the reality and prospects of mobility of students at the Algerian University under the application of the LMD system. "To know this, we started from a general hypothesis and four procedural hypotheses. The study sample consisted of (130) students between foreign and Algerian students. In order to collect data, both the form and the interview were used according to the comparative descriptive method and data analysis In the end, the Algerian university has a policy of closure and has no prospects of attracting foreign students to it. Those who are present are in the framework of providing assistance to the governments of these students or within the framework of an agreement. As for our Algerian students, Is seeking partnerships with developed countries to send them to foreign universities for Algeria to benefit from their experience